A Capabilities List for Equitable Transitions to University: A Top-down and Bottom-up Approach. Issue 2 (2nd April 2016) - Wilson-Strydom, Merridy
Abstract : Located within the context of equitable higher education as an enabler of human development, this paper presents a two-pronged approach to the development of a capabilities list for equitable transitions to university in South Africa, as an example of the global South. Drawing on an extensive analysis of the literature on access, participation, readiness and educational transitions, together with quantitative and qualitative data collected from high school and first-year university students, a list of seven capabilities is proposed. The paper demonstrates how the process-based methodology used satisfied all five criteria for the development of capabilities lists proposed by Robeyns (2003). Through the bringing together of top-down and bottom-up approaches in the formulation of the list, the methodology presented here provides a means of avoiding the pitfalls of omission and power (Nussbaum 2000), as well as ensuring space for participation and dialogue (Sen 2004).